FOUR-DIMENSIONAL INCOMMENSURATELY MODULATED STRUCTURE OF THULIUM POLYPHOSPHATE - Ma, Fa-xue; Zhao, Dan; Yang, Hong; Chen, Peng-Fei; Yang, Rui-Juan; Wu, Shan-Xuan (Journal of the Chilean Chemical Society, 2016)
Single crystal of rare-earth polyphosphate Tm(PO3)3has been grown under high temperature molten-salt method and structurally characterized by single crystal X-ray diffraction analysis. Using the four-dimensional superspace formalism for aperiodic structures, we performed the crystal structure refinement of Tm(PO3)3as (3+1)-dimensional incommensurately modulated structure with monoclinic superspace group C2/c(0, 0.358, 0)s0 and a = 14.0620 (12) Å, b = 6.6612 (6) Å, c = 10.0191 (9) Å, β = 127.6043 (9)0, V = 743.51 (11) Å3, Z = 4, Mr= 405.8, Dc= 3.626 g/cm3, F(000) = 744, μ(moKa)= 12.60 mm-1, R = 0.048 and ωR = 0.050. The structure features infinite chains of corner-sharing PO4tetrahedra which are affected by positional modulation running along the b-axis. The final structure model was reasonable and did not show any unusual features.